2011
DOI: 10.1007/s00383-011-2958-5
|View full text |Cite
|
Sign up to set email alerts
|

Residual aganglionosis after pull-through operation for Hirschsprung’s disease: a systematic review and meta-analysis

Abstract: This meta-analysis reveals that RA and TZB are the underlying causes of persistent bowel symptoms in one-third of all patients with HD requiring redo PT operation. Most patients have a satisfactory outcome after redo operation. Rectal biopsy should be performed in all patients with recurrent bowel problems after PT operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 47 publications
1
38
1
1
Order By: Relevance
“…Friedmacher and Puri [13] reported in a recent review that residual aganglionosis and transition zone bowel are the underlying causes of persistent bowel obstruction symptoms in about one-third (34.8%) of all patients with HD requiring a redo pull-through operation. We [14] reported in 2008 that transanal Soave procedure had the benefits of less body damage, lower costs, fewer complications compared with conventional Soave and IkedaSoper operation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Friedmacher and Puri [13] reported in a recent review that residual aganglionosis and transition zone bowel are the underlying causes of persistent bowel obstruction symptoms in about one-third (34.8%) of all patients with HD requiring a redo pull-through operation. We [14] reported in 2008 that transanal Soave procedure had the benefits of less body damage, lower costs, fewer complications compared with conventional Soave and IkedaSoper operation.…”
Section: Discussionmentioning
confidence: 98%
“…The patient's overall conditions should be considered including the type of previously failed procedure, level of anastomosis, rectal blood supply and fibrosis or inflammation of the pelvic and perirectum. The great majority used redo pull-through procedures in a recent meta-analysis are Duhamel, conventional and transanal Soave [13].…”
Section: Discussionmentioning
confidence: 99%
“…Munakata et al 22) reported that most cases of both severe Hypo and IND are not ultra-short type but short type from the rectum to the recto-sigmoid colon, and both severe Hypo and IND are more frequently associated with severe symptoms of bowel dysfunction than the other histological types. In general, ARM is not useful for patients with long segment type of HD, severe Hypo or IND [13][14][15][16]21) . In our results of ARM in patients at 2.6 years follow-up, about three quarters of the patients (short type of H disease, Hypo, and IND) had achieved good improvement 8) .…”
Section: Clinical Characteristics Before and After Arm In Patients Wimentioning
confidence: 99%
“…Anorectal myectomy (ARM) is appropriate for treatment in patients with outlet obstruction including ultrashort or short-type of Hirschsprung's disease (HD; aganglionosis), the allied disorders of HD such as hypoganglionosis (Hypo) and intestinal neuronal dysplasia (IND), and patients with high internal anal sphincter pressure [10][11][12][13][14][15][16] and encouraging results have been reported in children with short-type of HD and its allied disorders [17][18][19][20] . Short or ultrashort type of HD and its allied disorders with colonic inertia, who have a very slow cecum to rectum transit, may still be constipated after ARM 12,21) . ARM has been used for the histological diagnosis of patients in consecutive series of chronic constipation by most pediatric surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Yöntemin uygulanabilirliği, ameliyat süresi ve komplikasyonları açısından diğer yöntemlerle karşılaştı-rıldığı çok sayıda çalışma vardır (2)(3)(4)(5)(6) . Uzun segment Hh'lı hastalarda, serbestleştirmenin-ameliyatın temel ilkesine görece ters düşmekle birlikte-laparatomi/laparoskopi yardımıyla yapılabilmesi yöntemin daha geniş bir hasta grubunda kullanılmaya başlanmasına yol açmıştır (7)(8)(9)(10)(11) .…”
Section: Introductionunclassified